Sacred Legitimacy and Political Failure: Religion in Balthasar Klau’s Movement in Southern Belu, 1950–1965 - Muhammad Jaris Almazani; Febi Setiyawati; Muhammad Lodhi Firmansyah (Journal of Religion and Decoloniality, 2025)
The makdok movement led by Balthasar Klau in Southern Belu (1950–1965) reflected complex religio-political dynamics that went beyond mere heresy or local political events. Previous studies on Klau have largely emphasized historical perspectives, leaving a gap in understanding the symbolic meanings and spiritual role of the makdok as an instrument of political resistance in postcolonial society. This gap highlights the need for an anthropological inquiry into how Tetun cosmology, Catholic symbols, and modern political networks (PKI and BTI) were interwoven. The main research question addresses how the makdok functioned as an alternative authority negotiating power relations between adat, the Church, and the state. This study employed a qualitative-descriptive approach with its locus in Southern Belu, using an ethnohistorical method through archival research, literature review, and field testimonies. Data analysis was conducted interpretively within the framework of symbolic and political anthropology (Geertz, Comaroff & Comaroff). The findings reveal the hybridity of religious and political authority that constructed a utopian imagination of a world without labor, fair economic distribution, and promises of prosperity from the sea. The novelty of this study lies in the concept of a “political makdok” as a form of decolonialism from below. Recommendations emphasize further studies on the interrelation between local spirituality and modern organizations, as well as the potential of hybrid authority to form alternative models of power in postcolonial contexts.